Farelo de algodão e DDG com enzimas para suínos na fase de terminação - Pereira, Gabriel Henrique Marques (2021)
Some co-products, such as cottonseed meal (CM) and dried distillers grains (DDG) have been used to feed pigs to replace soy meal, however, because they have less digestibility than soy meal can affect the performance of animals. The use of dietary enzymes aims to increase the efficiency of the use of nutrients and improve the performance of animals. Thus, two tests were carried out, the first aiming to determine the digestibility coefficients (DC) of the control diets and containing CM and DDG with and without enzymes and the second to evaluate the performance and carcass characteristics of the pigs in the finishing phase. In the first trial, 30 castrated male pigs, with an average weight of 49.77 ± 3.83kg, were housed in metabolic study cages to determine the dietary DCs using the total feces collection method. The diets were: control diet (CD), diet with cottonseed meal (DCM) and diet with DDG (DDG), these with and without enzymes, totaling 6 treatments. In the second trial, 54 male castrated pigs, with an average weight of 51.96 ± 3.62 kg, were housed in masonry stalls receiving the same diets as the digestibility experiment with free feeding. The animals, the feed provided and the leftovers were weighed to determine AGD, ADFI and FC. At the end of the experimental period, the animals were fasted with solids and were slaughtered to collect data on HCW, CCW and CR, in addition to the weight of the organs, stomach, pancreas, liver and intestines. The animals were distributed in a randomized block design in a 3x2 factorial scheme. There was an interaction effect for the DC of CP, MM and total P. The use of enzymes increased DCCP for DDG, DCMM for CD and DCPtotal for DCM, while reducing DCPtotal for CD. The CD and DCM diets had higher DCDM and DCEE than DDG. DCNDT was higher in CD than in DDG, and DCM was similar to both (P <0.05). There was no difference for DCCa, DCCF and DCCE (P> 0.05). ADFI and ADG in period 1 were higher for CD than for DDG, whereas DCM was similar between both. In period 2, there was an interaction between the factors, and the diet with DDG worsened the AC. ADFI and ADG were higher for CD than for DCM and DDG (P <0.05). In period 3, there was no difference between treatments (P> 0.05). The HCW was higher for CD, when compared to DCM and DDG, similar behavior for CCW, with CD being greater than DDG and DCM similar to the others (P <0.05). There was no difference between CR and organ weights between treatments (P> 0.05). The use of cottonseed meal does not affect the digestibility and performance of the finishing pig diet. DDG provided worse digestibility and performance for finishing pigs in relation to soybean meal.